2020
DOI: 10.5937/jpea24-25505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osmotic dehydration and starch coating on the microbiological stability of apples

Abstract: This paper examines the effect of starch coating and the osmotic dehydration in sugar beet molasses on the microbiological stability of apples. One-half of the osmotically treated/untreated apples were protected by starch coating, resulting in four sample groups (namely the K, P, OD and OD+P sample groups). E. coli, Salmonella spp. and Listeria monocytogenes were not detected in any of the samples. Enterobacteria were present in the K and P samples in the first four days (indicating a downward trend), but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…As presented in Table 5, the microbiological analysis showed that Escherichia coli, Enterobacteriaceae, Salmonella spp., Listeria monocytogenes, Clostridium perfringens, and the total number of yeast and molds were not detected in any of the tested samples. These findings are in agreement with other studies, which showed that osmotic dehydration treatments have a highly reductive effect on most microorganisms [83,84]. However, based on the data obtained by the ISO method, it was found that the total number of microorganisms of osmotically dehydrated beets and osmotically dehydrated beets coated with Camelina sativa biopolymer at day 0 amounted to 2600 CFU/g and 2400 CFU/g, respectively.…”
Section: Storage Stabilitysupporting
confidence: 92%
“…As presented in Table 5, the microbiological analysis showed that Escherichia coli, Enterobacteriaceae, Salmonella spp., Listeria monocytogenes, Clostridium perfringens, and the total number of yeast and molds were not detected in any of the tested samples. These findings are in agreement with other studies, which showed that osmotic dehydration treatments have a highly reductive effect on most microorganisms [83,84]. However, based on the data obtained by the ISO method, it was found that the total number of microorganisms of osmotically dehydrated beets and osmotically dehydrated beets coated with Camelina sativa biopolymer at day 0 amounted to 2600 CFU/g and 2400 CFU/g, respectively.…”
Section: Storage Stabilitysupporting
confidence: 92%
“…9 Another study investigated effects of plasticizer (sorbitol) contribution on structural, barrier and mechanical properties of corn starch-based edible films. 10 In a recent study, films from jackfruit seed starch have been developed with glycerol having low opacity, high mechanical characteristics and average water vapour permeability. 11 In another study, aliginate films with glycerol, tributyl citrate (TC) and their blends have been made wherein films with glycerol were less hygroscopic when compared to films with TC or their blends.…”
Section: Applications Of Various Bio-based Plasticizersmentioning
confidence: 99%